CULTURAL PROFILE, BELIEFS AND PRACTICES, ATTITUDE TOWARDS LITERACY EDUCATION AND AGTA PROBLEMS AND ASPIRATIONS: INPUT TO AGTA LITERACY PROGRAM - Luna, Gabriel L. (International Journal of Psychosocial Rehabilitation, 2020)
Negritos are called the Agta of the Sierra Madre Mountains in Isabela, particularly at Sitio Diwagden at San Jose, San Mariano, Isabela, Region 02 Philippines. The research aimed to determine the cultural profile, beliefs and practices; attitude towards literacy education, and Agta problems and aspirations along education, thus, the research served as input for Agta Literacy Program. Findings concluded that as regards Agta cultural profile, the Agta adopted their name from the prominent people; The Agta dialect is Upos; They live in a simple and temporary shelter; The male Agta served as the head and provider of the family while the female Agta helped in the child rearing and housekeeping. The Agta prefers to eat foods that are found in their environment. The Agta leisure activities include bonding with their fellow Agta, and chewing betel nuts or momma or nganga. Agta have rich cultural heritage on the cycle of life relative to conception, childbirth, child rearing, courtship, marriage and death and burial. Agta are generally illiterate. They showed positive and very favorable attitude towards literacy education. The stakeholders and the Local Government Unit are supportive of Agta education. Agta have problems and aspirations especially on matters related to the education of their children and The Agta Literacy Program for the Adult-Agta and for the In-School-Agta was formulated to make every Agta literate at Sitio Diwagden, San Jose, Isabela.